OPTIMASI ALAT PEMANGGANG SATE DENGAN PENGATURAN KECEPATAN ALIRAN UDARA - , Endy Triyannanto, S.Pt ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research was conducted to determine effect of velocity air regulation with hardness, colour of sate product using gridiron. Research using gridiron with sonokeling charcoal and main substance sirloin goat meat witn the slaughtering age under one year. Research program using 4 treatment on the velocity air regulation: standart, 2 m/s, 4 m/s, 6 m/s with 5 minutes roasting time. Sate product tested in: hardness, colour, and organoleptic to determine whether the most interesting product. Research result was: (1) there were significant influence on the sate kambing hardness with the gridion. The faster velocity air regulation on gridion the harder it made, velocity air regulation on standart roaster (1,56 m/s) resulted hardness 1,65 N, 2 m/s resulted 1,50 , 4 m/s resulted 1,90 N and 6 m/s resulted hardness in 2,26 N (2) Velocity air regulation on the gridion influenced in product colour, the faster velocity air regulation the darker product has: velocity air regulation on the standart roasting produce L value 21,8